2014
DOI: 10.1001/jamasurg.2014.77
|View full text |Cite
|
Sign up to set email alerts
|

Time to Appendectomy and Risk of Perforation in Acute Appendicitis

Abstract: IMPORTANCE In the traditional model of acute appendicitis, time is the major driver of disease progression; luminal obstruction leads inexorably to perforation without timely intervention. This perceived association has long guided clinical behavior related to the timing of appendectomy. OBJECTIVE To evaluate whether there is an association between time and perforation after patients present to the hospital. DESIGN, SETTING, AND PARTICIPANTS Using data from the Washington State Surgical Care and Outcomes A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
170
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(192 citation statements)
references
References 36 publications
13
170
3
6
Order By: Relevance
“…Bickell et al [21] have reported that the risk for developing a perforated appendix is high when the period from the onset of symptoms to surgery exceeds 36 h. In a study of an elderly population, Omari et al [14] have reported that pre-hospital delay is higher in the perforated group (p<0.0001). In contrast, Drake et al [9] have found no relationship between the time to treatment and perforation. In our study,pre-hospital delay was higher in the perforated group (p=0.015).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Bickell et al [21] have reported that the risk for developing a perforated appendix is high when the period from the onset of symptoms to surgery exceeds 36 h. In a study of an elderly population, Omari et al [14] have reported that pre-hospital delay is higher in the perforated group (p<0.0001). In contrast, Drake et al [9] have found no relationship between the time to treatment and perforation. In our study,pre-hospital delay was higher in the perforated group (p=0.015).…”
Section: Discussionmentioning
confidence: 89%
“…There is a need for objective tests for a definite diagnosis. Despite the use of a variety of objective diagnostic methods, such as radiological imaging, laboratory tests, and scoring systems, in the diagnosis of complicated appendicitis and studies [8][9][10][11] of factors affecting the risk of perforation in AA, such as body mass index (BMI), gender, age, season, and time to appendectomy, no comprehensive study has examined the risk factors directly related to perforation. Therefore, we investigated the factors associated with perforation in AA, such as BMI, the physical parameters and location of the appendix and time to operation.…”
mentioning
confidence: 99%
“…For appendicular perforation emergency appendicectomy with peritoneal lavage is sufficient. 9 Nowadays iatrogenic perforations are common due to minimally invasive or endoscopic procedures. The incidence of perforation due to upper GI scopy was 1.2%.…”
Section: Discussionmentioning
confidence: 99%
“…However, Drake el al. 29 showed that perforation was not associated with elapsed time from hospital presentation to operating room start among adult patients. This result is compatible with the view that disease progression in appendicitis has a more complex pathophysiology and complicated appendicitis may be a separate biological or host-response entity.…”
Section: Rocmentioning
confidence: 93%
“…This result is compatible with the view that disease progression in appendicitis has a more complex pathophysiology and complicated appendicitis may be a separate biological or host-response entity. 29 Laboratory markers may contribute to the diagnostic process of AA however they can not to change the diagnosis of suspected cases on their own. When they used in a combination with physical examination, medical history and radiological findings they show greater promise.…”
Section: Rocmentioning
confidence: 99%